Problems to Improve Students’ Performance on Speaking at Theologian Students - Gulo, Eva Febriana Citranita; Sipayung, Kammer Tuahman (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2024)
The purpose of this research is to find out the students’ speaking performance problems in linguistics and non-linguistics. The research was done under a descriptive and qualitative methodology. The subject of this research was the first-semester (38) students at STT Syalom Nias. The data was collected through a questionnaire. The result showed that 66% of them had problems in non-linguistic problems.  The students felt worried that they made some mistakes during the speaking performance, they felt anxious, nervous, and uncomfortable to do the speaking performance. Problems in linguistics are 34%, they are grammatical errors, which make their speaking performance not fluent in speaking, especially when giving presentations and having conversations. The dominant problems that they faced were non-linguistic. It’s suggested to the students to practice speaking alone or in a group.